An NMR-based metabolomic approach to the analysis of the effects of xenobiotics on endogenous metabolite levels in plants. Issue 2 (2004) - Bailey Bailey, Nigel J. C. Nigel J. C.; Oven Oven, Matjaz Matjaz; Holmes Holmes, Elaine Elaine; Zenk Zenk, Meinhart H. Meinhart H.; Nicholson Nicholson, Jeremy K. Jeremy K.
Abstract : High field 1 H NMR spectroscopy has been employed to obtain, in conjunction with chemometric analysis, information regarding fluctuations in endogenous metabolic profiles for Crotalaria cobalticola plant cells following exposure to cobalt chloride. Such 'metabolomic' type data analysis is often confounded by experimental, environmental or genetic factors that are not correlated to the classifications of interest and serve only to complicate the extraction of meaningful answers from a dataset. This work demonstrates the application of data filtering to remove extraneous data that result from spectrometer variation rather than being correlated with the classes of interest. Samples were analysed from Crotalaria cobalticola suspension cell culture following exposure to cobalt chloride using 2 spectrometers. Removal of confounding data due to spectrometer variation resulted in clear separation between control and dosed classes. It was then possible to use the model to determine key changes in biochemical status caused as a result of exposure to cobalt. Branched chain amino acids, succinate and secondary metabolite precursors phenylalanine and tyrosine were all higher in the control samples, whilst choline, glutamate, alanine and lactate were higher in the dosed samples.